2019
DOI: 10.3847/1538-4357/ab01cc
|View full text |Cite
|
Sign up to set email alerts
|

Radio Variability from a Quiescent Stellar-mass Black Hole Jet

Abstract: Relativistic outflows are believed to be a common feature of black hole X-ray binaries at the lowest accretion rates, when they are in their 'quiescent' spectral state. However, we still lack a detailed understanding of how quiescent jet emission varies with time. Here we present 24 years of archival radio observations (from the Very Large Array and the Very Long Baseline Array) of the black hole X-ray binary V404 Cygni in quiescence (totalling 150 observations from 1.4 -22 GHz). The observed flux densities fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 93 publications
6
22
0
Order By: Relevance
“…The major argument in favour of a BH scenario is that the L R /L X ratio is consistent with the scatter of the L R − L X correlation for quiescent stellar-mass BHs, from Gallo et al (2014). The radio spectral index is not well constrained (α = −1.3 +0.6 −0.7 ) but could be marginally consistent with the flat-to-inverted spectrum observed in quiescent systems (see e.g., Plotkin et al 2019b), interpreted as self-absorbed synchrotron emission from a collimated jet. The low X-ray luminosity (L X (1 − 10 keV) = 7.5 +4.6 −3.5 × 10 29 erg s −1 ; Tab.…”
Section: A Quiescent Black Hole (Bh) X-ray Binarymentioning
confidence: 76%
“…The major argument in favour of a BH scenario is that the L R /L X ratio is consistent with the scatter of the L R − L X correlation for quiescent stellar-mass BHs, from Gallo et al (2014). The radio spectral index is not well constrained (α = −1.3 +0.6 −0.7 ) but could be marginally consistent with the flat-to-inverted spectrum observed in quiescent systems (see e.g., Plotkin et al 2019b), interpreted as self-absorbed synchrotron emission from a collimated jet. The low X-ray luminosity (L X (1 − 10 keV) = 7.5 +4.6 −3.5 × 10 29 erg s −1 ; Tab.…”
Section: A Quiescent Black Hole (Bh) X-ray Binarymentioning
confidence: 76%
“…While they did not attempt an overall spectral fit, Dinçer et al (2018) were the first to report a highly inverted radio spectrum, between 5-22 GHz, with α = +0.70 ± 0.13. Taken at face value, this spectrum is inconsistent with an extrapolation of the known mid-IR excess to radio frequencies; in the absence of mm data, however, it could either signal a highly peaked radio-mm spectrum, or simply trace high-level variability, or, the low frequency curvature of an otherwise ∼flat 50 µJy spectrum above 20 GHz, (as seen, e.g., in V404 Cygni; Russell et al 2013a;Plotkin et al 2019). Figure 3 shows the broadband SED of A0620-00 for three of the multi-wavelength campaigns discussed above: red open triangles correspond to the 2003-2005 campaign reported by Gallo et al (2007;VLA, SMARTS and Chandra), including the Spitzer data from Muno & Mauerhan (2006); green open squares refer to the 2013 campaign (VLA and SMARTS) reported by Dinçer et al (2018); blue filled circles represent the most recent data set, consisting of the new VLA, ALMA and SMARTS observations presented in this work.…”
Section: A0620-00's Jet: Spectral Extent and Variabilitymentioning
confidence: 80%
“…MeerKAT radio observations show a negative spectral index α = -0.8±0.4 in the quiescent state favoring an optically thin emission in contrast to the constantly flat spectra (α ∼ 0.35) that seems to dominate the outburst phase of GX 339-4 (Tremou et al in prep.). Although, radio emission in quiescence denotes the presence of hard state jets, the wide range of spectral indices that have been previously seen, it is not fully understood (Plotkin et al 2019) and it may be related with non-canonical jet geometry. Slightly negative spectral index could be seen in the case of a decelerating or a slowly expanding jet, while an inverted spectrum (eg: A0620-00; Dinçer et al 2018) could be generated due to the fast expanding parts of the jet (outer regions of the jet).…”
Section: Discussionmentioning
confidence: 99%
“…During such states, one has the opportunity to study the accretion process and the accretion-powered jets in a regime where the thermal emission from the thin disc does not outshine the radiation from non-thermal processes, which might have a fundamental role in the disc-jet coupling. Also, it has been recently shown that the quiescent state can show significant variability (e.g:, Miller-Jones et al 2008;Hynes et al 2009;Froning et al 2011;Wu et al 2016;Plotkin et al 2019).…”
Section: Introductionmentioning
confidence: 99%